Metaphor and entertainment a corpus-based approach to language in chinese online news - Han, Chong; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Metaphor and Entertainment presents the very first, large-scale exploration of metaphor in Chinese online entertainment news, one of the most vibrant and controversial news genres in contemporary China.
Keywords: Linguistics; Communication; Applied linguistics; Sociolinguistics; Translation and interpretation; Discourse analysis; Linguistics; Discourse Analysis; Sociolinguistics; Media Studies; Translation; Applied Linguistics; Communication Studies